IMPLICAÇÕES DO ENSINO MÉDIO INTEGRADO PARA A FORMAÇÃO DO TRABALHADOR: uma análise no Instituto Federal de Educação, Ciência e Tecnologia do Maranhão IFMA Campus São Luís Monte Castelo - Pedrosa, Elinete Maria Pinto (2013)
In this work, we investigate the implications of the "Ensino Médio Integrado" to worker formation, in one analisis at Instituto Federal de Educação, Ciência e Tecnologia do Maranhão- IFMA , Campus São Luís Monte Castelo.The object of study is the Technical Course on Computer Integrated high school.Thus, secondary and vocational education in Brazil since the first state initiatives, has been characterized by a structural duality, constituting two networks of differentiated teaching, one focused on general training and the other for professional.The Law of Guidelines and Bases of National Education Law No. 9.394/1996, enacted in a context marked by the correlation of forces, paved the way for high school reform and professional,signaling for a type of training aligned to the prescriptions of neoliberal ideological current.Decree No. 5.154/2004, which revoked Decree 2.208/1997, brought the possibility of the integration of vocational education to high school,based on a single curriculum proposal that, in an integrated manner, assure the fulfillment of the objectives established for general education and the preparation conditions for the exercise of technical professions.In this context, we investigated the challenges and prospects for achieving the goals of integrated training and that implications have brought to worker training.The objective was to analyze the implications and explicit elements that hinder the realization of this proposal.We as a theoretical contributions of Marx (1983.1992), Engels (1983), Gramsci (1991, 1995, 2001), Pistrak (1981),Frigotto (1988, 1998, 2001, 2005, 2006), Kuenzer (2000, 2001, 2002, 2005), Ciavatta (2005), Ramos (2002, 2005), among others. The locus of The study as the campus IFMA - São Luís Monte Castelo.The research subjects were teachers and students from the Technical Course on Computer Integrated.Used as instrument to collect data open and closed questionnaires.It was found in the analysis of data from the object of our study, the Technical Course in Computing,the Secondary Campus Integrated IFMA Monte Castelo São Luís is not forming to work and yes,preparing students for ENEM where they target a graduation,where they target a graduation, mostly to medical school or law school.Then one realizes that the proposed integration of the mentioned course can be more effective for education be understood coherently, where young people can have access to the domain knowledge that may allow a cognitive training and development,beyond a critical view of reality that is called, including to combat it.